Global environment outlook 3. (United Nations Environment Programme, 2002)
Este CD contiene estadísticas nacionales, regionales y globales elaboradas por la UNEP en el GEO-3, entre las cuales están: Complete GEO-3 report in Adobe PDF format, GEO-3 electronic reference system, GEO-3 Data compendium, 290 time series indicators for 249 countries and aggregations.